A Model of Utility Smoothing - Wakai, Katsutoshi (Econometrica, 2008)
Experimental studies have found that a decision maker prefers spreading good and bad outcomes evenly over time. We propose, in an axiomatic framework, a new model of discount factors that captures this preference for spread. The model provides a refinement of the discounted utility model while maintaining dynamic consistency. The derived discount factors incorporate gain/loss asymmetry recursively: the difference between average future utility and current utility defines a gain or a loss, and gains are discounted more than losses. This notion of utility smoothing can induce a preference for spread: if bad outcomes are concentrated on future periods, moving one of the bad outcomes to today would be beneficial because such an operation eliminates a large loss and replaces it with a small gain.